Development of Mocaf-Wheat Noodle Product with the Addition of Catfish and Egg-White Flours as an Alternative for High-Animal-Protein Noodles - Friska Citra Agustia; Yovita Puri Subardjo; Gumintang Ratna Ramadhan (Faculty of Animal and Agricultural Sciences, Diponegoro University, 2019)
This study aimed to determine the best formula and chemical dan sensory properties of noodles made from mocaf-wheat flour supplemented with catfish and egg-white flours. The factorial randomized trial was used in this experiment. The treatment factors consisted of the types of supplementary flour i.e. catfish flour (T1) and egg white flour (T2). These supplementary flour was applied to the mocaf and wheat flour of 70:30 as follows 5, 10, 15, and 20% (w/w) and assigned as P1, P2, P3, and P4. Chemical properties (water content, total fat, total protein, carbohydrate, and ash contents) and sensory properties were then analyzed. Hedonic test was performed to determine the consumer’s acceptance level of 15 semi-trained panelists. Result showed that the interaction between the two treatments (TxP) had no significant effect on the five chemical variables, while combination of the two treatments (TxP) only had a significant effect on the texture of mocaf-wheat noodles and had no significant effect on other variables. Noodle with the treatment of egg white flour supplementation had higher protein content compared to those of catfish flour. As more flour was supplemented, the higher protein content. As conclusion, the mocaf-wheat noodle product was able to be developed to produce high protein content of noodle.